Poplars in agroforestry: A journey of success - Chandra, J.P. (Indian Journal of Agroforestry, 2020)
The capability of quick growing exotics to generate high income derived systematic approach for introducing Poplars in agroforestry. In the beginning evaluation trials were conducted to identify suitable clones. Thereafter, exotic clones were multiplied and supplied to farmers with defined package of practices. The hybridization programme was a real breakthrough for success of Poplars in agroforestry besides establishment of wood based industries and credit facility from NABARD.